Towards an innovative combined process coupling biodegradation and photo‐oxidation for the removal of pharmaceutical residues. Issue 3 (27th October 2020) - Joannis‐Cassan, Claire; Rodriguez Castillo, Alfredo S; Dezani, Chloé; Gómez‐Canela, Cristian; Reoyo‐Prats, Brice; Calas‐Blanchard, Carole; Barata, Carlos; Lacorte, Silvia; Plantard, Gaël
Abstract: BACKGROUND: The occurrence of pharmaceutical compounds in wastewater has become a major concern for human health and the environment. Therefore, it is an important challenge to improve conventional wastewater treatment to remove these compounds. Coupling biological treatment with advanced oxidation technology has been widely studied in the literature, but only sequential associations of the two processes have been used. This study proposes an innovative concept based on a real integration of the photocatalytic oxidation process in a continuous recycling loop on a membrane bioreactor. The role of the oxidation here is not to completely degrade pharmaceuticals, but instead to oxidize them moderately to increase their biodegradability so that they can be eliminated by the biological process. RESULTS: Preliminary experiments on the oxidation process indicated that a flux density of 5 W m −2 was sufficient to increase biodegradability and decrease the toxicity of a cocktail of three pharmaceuticals. Then the performance of a 20‐L continuous membrane bioreactor treating wastewater with seven pharmaceuticals, without and with pre‐oxidation at 5 W m −2, were compared. Pre‐oxidation increased the global removal for some recalcitrant pharmaceuticals (from 3% to 47% for diclofenac and from 1% to 44% for furosemide) without affecting either the removal of carbon, nitrogen or phosphorous by activated sludge, or of already highly removed pharmaceuticals. CONCLUSION: This work proves the feasibility of an innovative concept of a continuous hybrid process coupling a photocatalytic oxidation process and a membrane bioreactor for the treatment of pharmaceuticals in wastewater, with low cost and size. © 2020 Society of Chemical Industry (SCI)